HUBUNGAN PERSEPSI TENTANG MUTU PELAYANAN DENGAN MINAT KUNJUNGAN ULANG PASIEN RUMAH SAKIT ROYAL PRIMA JAMBI - Pairi, Agus; Ginting, Marinawati; Silitonga, Sondang (SCIENTIA JOURNAL, 2018)
Government policy regarding national health insurance (JKN) has triggered an increase in the growth of the health services sector, where JKN has provided broad opportunities for Indonesians to access health services. As an impact, there was an over demand so that the development of the hospital industry experienced a rapid growth and almost all hospitals participated in "enjoying". This study aims to determine the relationship of perceptions of service quality to the interest of returning patients to the Royal Prima Hospital. The method used in this research is analytical survey method with cross sectional approach. The population in this study were all patients who visited the outpatient installation, the number of samples was 196 respondents, with the sampling technique using purposive sampling. The instrument used for data collection is a questionnaire. The results of the analysis showed that there were 35 (74.5%) patients with poor perceptions of service quality interested in revisiting ( and among patients who assessed the quality of hospital services there were 143 (96.0%) interested in revisiting (Repeated Patient). Based on the results of the chi-square statistical test, the value of p <α (p = 0,000) means that at α = 5%, it can be concluded that there is a significant relationship between perceptions of service quality and interest in revisiting patients. It is expected that outpatient installation officers will improve service quality so that patients are interested in revisiting (Repeated Patient).